Design of Interactive Tourism Games in Rammang-Rammang Based on Construct 2 - Hanafi, Muh. Alfian; Hanafi, Hamsu; Fathahillah; Darma, Dyah (Politeknik Pariwisata Lombok, 2026)
Introduction: This research aims to combine creativity and interactive game technology in expanding persuasive measures and efforts to promote Rammang-Rammang tourist destinations, make a significant contribution to the development of Indonesia's tourism sector, and demonstrate the importance of adapting to technological developments in this digital era. Methodology: The research method used is Research and Development (R&D) with the application of the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation. Data were collected through interviews, questionnaires, and documentation studies. The data analysis was conducted using both qualitative and quantitative descriptive methods. Findings: Based on the interviews with informants, the game product was considered good as it successfully created a software product that promotes a tourist destination using a technological approach. The evaluation covered two aspects: (1) system functionality, which was deemed good, and (2) usability testing, which was conducted with 20 respondents, yielding an average usability percentage of 91.2%. This score is considered excellent. Conclusion: Based on the data collected, it can be concluded that the game product developed is considered valid and feasible according to ISO 25010 testing.